Relationship between Psychological Empowerment with Faculty Members’ Interest in Growth Programs with Mediating Role of Intrinsic Motivation - حمید رحیمی; راضیه آقابابایی (مطالعات منابع انسانی, 2019)
Background and Objective: The effective execution of growth programs for faculty members can improve their productivity and academic excellence. Therefore, this study analyzed the relationship between psychological empowerment and faculty members’ interest in growth programs with the mediating role or intrinsic motivation. Methodology: This is an applied descriptive-correlational study, in which the statistical population included 303 faculty members of Kashan University. The stratified random sampling method was employed to select 187 members as the statistical sample. Data collection was performed through a questionnaire, the validity of which was evaluated through construct and content validity tests. Data analysis was then done in SPSS and AMOS at descriptive and inferential levels. Findings: The mean of the studied variables was above the average. Moreover, the mediating role of intrinsic motivation was positive and significant in the relationship between empowerment with growth of faculty members. Conclusion: University managers can improve the psychological empowerment prerequisites of faculty members to enhance their motivation for participation in growth programs and lay the foundations for their growth and academic dynamism.